Design of Enterprise Production and Sales measures and Forecast Information System Based on WEB - Gao Shuzhi; Zhao Na (Institute of Advanced Engineering and Science, 2014)
The enterprise supply of raw materials and production, sales, product information integration as a research object, on the basis of J2EE architecture and the Spring framework, building Web Based Enterprise production and distribution and prediction of multi-tier architecture ERP system. First, use spring+hibernate implementation of MVC design mode ; and, with mvc mode implementation of J2EE Multi - Application System schema, development function perfect enterprise sales management system ; last, use move average law, and Trend Forecast law, and index smooth law, and line type the most Xiaoping method and curve type the most Xiaoping method Five kind of algorithm average to sales accurate real - time forecast, decision sector can developed accurate production plan to effective guidance production job. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5470